Psychoanalysis of Lesbians and Gays in the Great Gatsby Novel - Alif Alfia Ufil Rahayu (Pioneer: Journal of Language and Literature, 2017)
In this qualitative research, the researcher only focused on the event or situation in the novel depicting lesbians and gays sigs. The researcher used The Great Gatsby novel as an object in this research. This research was aimed at one main purpose it was to depict the sign of lesbians and gays in the story of The Great Gatsby. The utterances in the dialogue of The Great Gatsby were used as the main data. All of the data were analyzed by using Lois Tyson’s theory. The results revealed that there were eight lesbian signs and seven signs of gay. In addition, the researcher got that there were consious type was dominated sign in this novel. The researcher expected to the next researcher could be did research on the lesbian and gay signs with the different types of this research.